2015
DOI: 10.1016/j.chom.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

CDK11 in TREX/THOC Regulates HIV mRNA 3′ End Processing

Abstract: SUMMARY Transcriptional cyclin-dependent kinases play important roles in eukaryotic gene expression. CDK7, CDK9 (P-TEFb) and CDK13 are also critical for HIV replication. However, the function of CDK11 remained enigmatic. In this report, we determined that CDK11 regulates the cleavage and polyadenylation (CPA) of all viral transcripts. CDK11 was found associated with the TREX/THOC, which recruited this kinase to DNA. Once at the viral genome, CDK11 phosphorylated serines at position 2 in the CTD of RNAPII, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 65 publications
0
45
0
1
Order By: Relevance
“…Although the polyA assay will detect read-through–5′ LTR–polyadenylated transcripts, the sevenfold excess of long LTR over polyA transcripts in the unstimulated cells suggests that if read-through–5′ LTR–polyA transcripts are present, they constitute less than or equal to one-seventh of the total. Although previous studies have reported the presence of non-polyadenylated HIV transcripts (13), low quantities of polyadenylated HIV transcripts (13, 52), and/or regulation of HIV transcription by 3′ end processing (58, 59), this block to completion has not been well described as a mechanism of latency, in part due to the lack of quantitative comparison between elongated and polyadenylated transcripts. Activation increased the absolute number of polyadenylated transcripts, the ratio of polyadenylated/total and polyadenylated/elongated transcripts (the latter often approached 1), and the frequency of cells with polyadenylated transcripts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the polyA assay will detect read-through–5′ LTR–polyadenylated transcripts, the sevenfold excess of long LTR over polyA transcripts in the unstimulated cells suggests that if read-through–5′ LTR–polyA transcripts are present, they constitute less than or equal to one-seventh of the total. Although previous studies have reported the presence of non-polyadenylated HIV transcripts (13), low quantities of polyadenylated HIV transcripts (13, 52), and/or regulation of HIV transcription by 3′ end processing (58, 59), this block to completion has not been well described as a mechanism of latency, in part due to the lack of quantitative comparison between elongated and polyadenylated transcripts. Activation increased the absolute number of polyadenylated transcripts, the ratio of polyadenylated/total and polyadenylated/elongated transcripts (the latter often approached 1), and the frequency of cells with polyadenylated transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Nef RNA/DNA tended to be higher than polyA RNA/DNA, which could indicate transcriptional pausing at the 3′ LTR and/or a block to polyadenylation. End processing of the viral RNA could be inhibited by pausing at the 3′ TAR stem-loop or low expression of HIV-1 Vpr, which modulates polyadenylation activity (60), or human cellular factors such as CDK11 (58, 59) and polyadenylation factors. Because polyadenylation facilitates nuclear export, stability, and translation (53), the lack of polyadenylated HIV RNA could contribute to the previously observed block in nuclear export of HIV RNA (47) and to low amounts of HIV protein.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of CPSF6, THOC5 directs its early recruitment to transcribed genes and, following THOC5 or CPSF6 loss, proximal poly(A) sites are preferentially used [113]. A further twist in the ‘tail’ arises from recent studies on CDK11 that triggers Ser2 phosphorylation of the Pol II CTD [114]. Ser2 phosphorylation peaks at the 3′-end of genes and this stimulates the recruitment of 3′-end processing factors to the gene.…”
Section: Recruitment Of Trex To Mrna Through Transcription and Rna Prmentioning
confidence: 99%
“…Cells were then transfected with the reporter pNL4-3.Luc plasmid (0.5 g) and 4 g of antisense oligonucleotide DNA corresponding to the anti-codon region of tRNA Arg (UCU) (TAGAAGTCCAATGCGCT ATCCATTGCG) or a randomized negative control (AGTCTTATGCTTGCCCAGCAGGCTAAA). At 24 h after transfection, virus production in culture supernatants was quantified by Gag p24 ELISA, and luciferase activity in cell lysates were measured as described previously (37). Gag p24 levels were normalized to luciferase activities.…”
Section: Methodsmentioning
confidence: 99%